2018
DOI: 10.1016/j.vaccine.2017.10.079
|View full text |Cite
|
Sign up to set email alerts
|

The generation of a simian adenoviral vectored HCV vaccine encoding genetically conserved gene segments to target multiple HCV genotypes

Abstract: Highlights This study describes HCV prophylactic vaccines designed to target multiple genotypes. HCV conserved immunogens were encoded within a simian adenoviral vector (ChAdOx1). Vaccines are highly immunogenic in mice and induce T-cells targeting multiple genotypes. HCV immunogens contain multiple human T-cell epitopes as defined in natural infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 53 publications
1
28
0
1
Order By: Relevance
“…(23,24) All strategies face difficulties dealing with the enormous genetic diversity of HCV, (3,25) leading to a recent focus targeting conserved HCV genomic regions. (26) Further questions on vaccine efficacy cannot be answered in chimpanzees because of a recent moratorium on using chimpanzees in biomedical research. (27) For these reasons, development of a small animal model is critically important for HCV vaccine development.…”
Section: And Peter Simmondsmentioning
confidence: 99%
“…(23,24) All strategies face difficulties dealing with the enormous genetic diversity of HCV, (3,25) leading to a recent focus targeting conserved HCV genomic regions. (26) Further questions on vaccine efficacy cannot be answered in chimpanzees because of a recent moratorium on using chimpanzees in biomedical research. (27) For these reasons, development of a small animal model is critically important for HCV vaccine development.…”
Section: And Peter Simmondsmentioning
confidence: 99%
“…Recent work has shown that vaccines can induce T cell immunity to conserved regions of the virus. 67 Both mechanisms of CD8+ T cell failure, T cell exhaustion and viral escape, are directly linked to the CD4+ T cell response. Indeed, during chronic infection, CD4+ T cells are only present at a very low frequency, display impaired proliferative and cytokine production, and are characterised by high expression of inhibitory receptors such as PD-1 and cytotoxic T-lymphocyte associated protein 4.…”
Section: Failure Of T Cell Immunitymentioning
confidence: 99%
“…The majority of currently registered clinical trials with a known status are of vaccines using T cell–mediated immunity (Table ) with some encouraging results from phase 2 studies . In addition, a recent preclinical study has characterized an adenoviral vaccine using conserved, immunogenic HCV epitopes to generate HCV‐specific T cell responses in mice across a range of HCV genotypes . Further progress in this field is eagerly awaited.…”
Section: Current Progress In Vaccine Developmentmentioning
confidence: 99%